Perceptions and practices of menstrual hygiene management among adolescent girls and young women in an urban underprivileged area of Bengaluru, India: a qualitative study - Shalini V., Sayvithaa; Johnson, Avita; Amalan, Joe (International Journal Of Community Medicine And Public Health, 2025)
Background: Menstrual hygiene management (MHM) is vital for the physical, emotional, and social well-being of adolescent girls and young women. In low- and middle-income countries, including India, cultural taboos and limited access to hygiene products create significant challenges. This study explores MHM perceptions and practices among adolescent girls and young women in Austin Town, Bengaluru, Karnataka, with a focus on cultural practices and barriers to effective MHM. Methods: A qualitative study was conducted between March and April 2023 with IEC study ref. no.110/2023 using focus group discussions (FGDs) with adolescent girls and young women (aged 13-30 years) from underprivileged areas of Neelasandra and Maya Bazar in Austin Town, Bengaluru. A total of 6 FGDs were conducted with 8-12 participants per group. Data were analysed using thematic analysis and inductive coding. Results: Key findings include the lack of prior awareness of menstruation for some participants, with family members and school as primary sources of information. Hygiene practices such as regular pad changes and washing external genitalia were commonly followed, though cloth pads were seen as unhygienic by some. Sanitation concerns, particularly in school washrooms, were prevalent. Cultural taboos regarding isolation, dietary restrictions, and participation in activities during menstruation were reported. Support from family varied, and there were mixed opinions on involving boys in menstruation discussions. Conclusions: The study highlights gaps in MHM, including limited knowledge, sanitation barriers, and cultural taboos. Public health interventions should focus on early education, improved facilities, and engaging boys and men to reduce stigma and promote equality.